Effect of social marketing mix and attitude on farmers’ flood preparedness behavior in the east coast of Malaysia - Gazali, Umar Muhammad (2018)
The agricultural sector in Malaysia is exposed to natural disasters such as flood, landslide, drought, thunderstorm and other natural catastrophes. Among these, flood stands to be the most important in East Coast of Malaysia. The 2014/2015 flood in the East Coast of Malaysia caused damages to several properties, lives, livestock and agricultural products such as paddy, vegetables and fruits worth billions of Malaysia ringgit. The most affected are the rural populace who are predominantly smallholder farmers. This affect their livelihood sources and income making life more difficult. The effect of flood on agricultural productivity in the area has been a subject for research for many years. This study has been purposely chosen because of limited research within the area with respect to empirically and theory driven research based on flood disaster preparedness. There is an obvious gap between how theories are recommending on creating awareness and motivating flood preparedness behavior among the smallholder farmers and how preparedness is actually undertaken. Attempts have been made on how to fill this gap between theory and practice. In most of the studies regarding flood preparedness, little emphasis is place on how behavioral theories are actually applied to motivate flood preparedness behavior. There are more focus on how preparedness will work rather than how preparedness is actually carried out. Studies have shown that attitude of farmers towards flood disaster preparedness behavior is found to be low because smallholder farmers lack the proper motivation to take preparedness actions. However, over the years, both the government, researchers and individuals have focused most on ex-post (post disaster) rehabilitation rather than on mitigation activities which reduces losses. Farmers therefore rely on the effort of government for rehabilitation during disaster. It is therefore necessary to conduct study on how social marketing mix will be used to create awareness to motivate the smallholder farmers towards embracing flood preparedness behavior. The objective of this research is to determine the effect of social marketing mix and attitude to motivate smallholder farmers’ flood preparedness behavior and the mediation role of intention in the relationship between farmers’ attitude and flood preparedness behavior. Data collection were done by the use of quantitative method through structured questionnaire using a systematic sampling technique. Four hundred and eighteen (418) smallholder farmers’ were selected from the states of Pahang, Kelantan and Terengganu. In each state, six districts were randomly picked. This constitute, Pahang (Kuatan, Pekan, Jerantut, Maran, Temerloh and Muazam), Kelantan (Tumpat, Tanah Merah, Kuala Krai, Pasir Puteh, Machang and Gua Musang) and Terengganu (Dungun, Besut, Setiu, Kuala Terengganu, Hulu Terengganu, and Marang). The respondents’ were smallholder farmers affected by the 2014/2015 flood disaster. The statistical package used for the analysis were SPSS version 22.0 and AMOS graphics software Version 22.0. Descriptive Statistic, Binary Logistic Regression, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), Measurement Model and Structural Equation Model (SEM) were tested. The structural equation modeling was used to evaluate the causal model while the confirmatory factor analysis was performed to examine the reliability and validity of the measurement model. The findings indicates that social marketing (product, price, place, promotion) and attitude significantly influence flood preparedness behavior. However, promotion mix construct was the strongest predictor among the exogenous variables. The study also found that intention partially mediates the relationship between 4Ps, attitude and flood preparedness behavior. The findings finally indicates that past experience of flood disaster and income have a significantly smallholder farmers’ flood preparedness behavior. Policy wise, the study can act as a platform for relevant agencies and policy makers to ensure proper management and development of its flood disaster preparedness activities. It will assist the government in the formulation of disaster management plans, policies and programs that will motivate and create flood preparedness awareness to public based on social marketing approach. The study concluded that the hypothesized model that social marketing mix 4Ps and attitude significantly affect smallholder farmers’ flood preparedness behavior in East Coast of Malaysia were supported.